WHO WAS THE MIGHTY DESIGNER OF THE COLD WAR? - Jovhar Museyibzada (Galaxy International Interdisciplinary Research Journal, 2022)
Cold war has always been a focal point in international relations studies, while the question of “how did it emerge at first place?” has been a source of constant debate. In this article, the author aims at answering the question by starting the analyses as early as 1917 October Revolution. It is concluded that polarization of the world in the hands of two superpowers with antagonistic ideologies made the cold war inevitable.